Association of non-HDL-C and depression: a cross-sectional analysis of the NHANES data - Zhu, Xianlin; Zhao, Yiwen; Li, Lu; Liu, Jiaoying; Huang, Qiankun; Wang, Suhong; Shu, Yanping (Frontiers in Psychiatry, 2023)
Objectives: Non-high-density lipoprotein cholesterol (non-HDL-C) has attracted attention because it is associated with a variety of diseases and is easy to measure. However, the relationship between non-HDL-C and depression is still unclear. Our aim was to assess the relationship between non-HDL-C and depression using the cross-sectional NHANES survey from 2005 to 2018. Methods: We examined the association between non-HDL-C and depression using weighted multivariable logistic regression models and subgroup analysis. Sensitivity analysis demonstrated the robustness of the results. Results: There were 42,143 participants in this study and 8.6% had depression (weighted 7.53%). Non-HDL-C was higher in participants with depression compared to those without depression (weighted mean 3.64 vs. 3.73, p<0.01). There was a positive association between non-HDL-C and depression with a 95% OR of 1.22 adjusted for multifactorial (95%CI,1.03-1.45). In subgroup analyses, non-HDL-C was positively associated with depression in men (OR, 1.31; 95% CI, 1.01-1.70), normal BMI (OR: 0.93; 95% CI: 0.66-1.32) and in participants without hypertension (OR, 1.29; 95% CI, 1.01-1.66). Conclusion: Non-HDL-C positively correlated with depression, and further research may be better for clinical service.